The Influence of Internationalization Degree on the Performance of Industry-Specific Companies: A Case Study of Taiwan (2001-2017) - Wei, Shih-Yung; Lin, Li-Wei; Gan, Su-Mei (International Journal of Economics and Financial Issues, 2019)
In this study, a total of 924 enterprises and 15708 companies were used for listed companies in 2001-2017, and two industries were identified as scientific and technological industries and traditional industries from the research samples, among which 556,9452 (60.17%) were in the science and technology industry and 6256 in traditional industries. The proportion of total sales of overseas sales was regarded as the index of internationalization. The results demonstrated that the influence of internationalization of the technology industry on the performance of companies exhibited an inverse U relationship, and the traditional industry exhibited a positive U relationship. Moreover, the international degree of the science and technology industry was more than 71.68%. The strengthening of internationalization will exert a negative impact on the performance of a company. In addition, traditional industry was more dependent on the domestic market, international reaches 38.49%, and the party can accelerate a company's performance. This finding is ascribed to that the effect of internationalization on the performance of a company differs markedly as long as the degree of dependence of the two industries in the international market and the domestic market is different. Keywords: international company performance; panel data electronics; company's performance JEL Classifications: C23, L25 DOI: https://doi.org/10.32479/ijefi.8191